A PLURIDISCIPLINARY APPROACH TO SCIENTIFIC INTEGRATION AND ITS APPLICATION TO CONTEMPORARY ISLAMIC EDUCATION - Hanif Satria Budi, M.; Naim, Ngainun; Akhyak (International Journal of Multidisciplinary Reseach, 2025)
The development of science and technology has brought significant impacts on Islamic education. One of these impacts is the challenge to reshape scientific paradigms to become more open, integrated, and interdisciplinary. This article aims to examine the essence and contribution of the pluridisciplinary approach within the process of knowledge integration and its application in Islamic education. The study employs a library research method by reviewing a range of relevant academic sources, including books, scholarly articles, conference proceedings, and institutional documents. The analysis was conducted through systematic stages, encompassing source collection, literature classification, content examination, and the formulation of a conceptual synthesis. The findings indicate that the pluridisciplinary approach plays an essential role in dismantling the divide between religious and general sciences. Through this approach, various disciplines—such as theology, sociology, psychology, and educational management—can interact on an equal footing to construct a comprehensive understanding of the realities of Islamic education. Its implementation can be observed in integrative curriculum development, collaborative cross-disciplinary learning, multidisciplinary research, and educational management that is responsive to globalization and digital technology advancement. The article concludes that the pluridisciplinary approach is not merely an analytical method but also serves as a philosophical foundation for developing an Islamic education system that combines spiritual, intellectual, and social values. This approach reaffirms the principle of the unity of knowledge in Islam, which holds that all knowledge originates from God and must be utilized for the benefit of humanity. Consequently, Islamic education can progress toward a holistic, humanistic system aligned with the demands of contemporary times.